Using institutional ethnography's ideological circle to portray how textually mediated disability discourse paralysed a Supreme Court of Canada ruling. Issue 4 (7th August 2016) - Deveau, Jean Louis
Abstract : Persons with disabilities created through texts as damaged goods are being 'cured' by workplace accommodation, a textually mediated work process. Prior to 1999, workplace accommodation in the Canadian federal public service signified the adjustments necessary to enable a disabled worker to fit into a workplace designed for able-bodied workers. In 1999, a Supreme Court of Canada (SCC) ruling known as Meiorin turned this accommodation provision on its head. Instead of being focused on individual-level fixes so that a disabled worker could be accommodated in an existing workplace, this legislation required employers to transform their workplaces so as to make them ready to receive as many different types of workers as reasonably possible from the outset. Using Dorothy E. Smith's institutional ethnography, I use my experiences as a disability rights activist employed in the Canadian federal public service to explicate how textually mediated disability discourse paralysed this groundbreaking SCC ruling.